Nutrition Interventions of Herbal Compounds on Cellular Senescence. (27th April 2022) - Chen, Zhongxu; Wu, Yixin; Lin, Qinlu; Cai, Jie; Liu, Xi; Liang, Ying
Abstract : When cells undergo large-scale senescence, organ aging ensues, resulting in irreversible organ pathology and organismal aging. The study of senescence in cells provides an important avenue to understand the factors that influence aging and can be used as one of the useful tools for examining age-related human diseases. At present, many herbal compounds have shown effects on delaying cell senescence. This review summarizes the main characteristics and mechanisms of cell senescence, age-related diseases, and the recent progress on the natural products targeting cellular senescence, with the aim of providing insights to aid the clinical management of age-related diseases.